The impact of cognitive load on lower limb biomechanics during the take-off phase before service in tennis players of different levels - Xuan, B.; Sun, D.; Li, F.; Cen, X.; Wang, Y.; Wang, D. (Journal of Sports Sciences, 2026)
This study examines the impact of cognitive load (CL) on lower limb biomechanics during the take-off preparation phase of the platform serve in tennis players of varying skill levels. Fifteen elite and fifteen amateur tennis players performed platform serves before and after completing a 30-minute Stroop task designed to induce CL. Key biomechanical parameters, including joint range of motion (ROM), joint moments, centre of mass (COM) displacement, and ground reaction force (GRF), were assessed using both kinematic and kinetic analysis.